Interlude: relieve - Lee, Audrey Si Ying (Nanyang Technological University, 2023)
Constructed with individual pieces of intricately papier-mâchéd tiles made from toilet paper, “Interlude: Relieve” is a serene space sculpted for one to rest and relieve themselves from the bustle of the world.